The Question of Moral Selection in French Ecclesialism (European Journal of Pedagogical Initiatives and Educational Practices, 2023)
As a result of the influence of time and space in the chain of thought development, we will learn about the emergence of various ideas and philosophical views through the history of philosophy, as well as the time and space in which we live, if possible, "We exist" understanding and observation was the purpose of this article. In the way of a philosophical analysis of what our existence and responsibility are in the existence we exist, in this article, the existence of man in the philosophical and moral views of Jean-Paul Sartre and Albert Camus, who witnessed two world wars of the 20th century, are the representatives of French existentialism. responsibility, freedom and choice in the "borderline situation" are observed.